Beliefs and Their Various Aspects in the Daily Life of the Sama Dilaut - ALOJAMIENTO, SHEILFA; QUILING - ARQUIZA, MUCHA SHIM; TIANNOK ENRIQUEZ, RIZALINA; ROS, MATILDA (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
Its original in Bisaya, and now coming with an English translation, this study is about the beliefs, worldview and histo,y of the Sama Dilaut community in Cagayan de Oro City. Outsiders call them Badjaos, they call them selves Sama Dilaut.Arriving sometime in 1994 or 1996 from Basilan, five families have become p ermanent residents of Lapasan, Cagayan de Oro, the rest, around forty families or more come, stay for a few months and go. Fonnerly fishermen in their place of origin, now they make a living begging or diving for coins at the pie,: In their new setting, they still manage to practice their customs and continue to uphold their values. They do not regard begging as shameful; but stealing is a major crime. New influences, like wanting to send their children to school, are showing.